Even faster web sites - Souders, Steve (O'Reilly, 2009)
"Speed is essential for today's rich media web sites and Web 2.0 applications. With this book, you'll learn how to shave precious seconds off your sites' load times and make them respond even faster"--P. 4 of cover.